Komposisi Karawitan ‘Dinamika Rumah Tangga’ - Wasiran - (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
“The Dinamika Rumah Tangga” Karawitan Music Composition. ’Household Dynamics’. The purpose ofthis creation is transforming the household dynamics in the form of karawitan musical composition. Dynamics embodiedin the form of rhythm, tempo, vocal, harmony, the arrangement of the stage, lighting, sound, costume andpuppet performances. Puppet performances are intended to enhance the audience’s imagination based on the musicalatmosphere, the lyrics and the fl ow of rhetoric. The composition is motivated by the story of Begawan Wisrawa,Danaraja and Goddess Lokati in a play ”Bedhahing Lokapala”. This work was inspired by the arrogant behavior,jealousy, hate, anger, lies, prejudice, exclusion of human rights and confl ict between characters.